Review of Recent Literature on Impacts of Agricultural R & D for Poverty, Nutrition, and Resilience. - Masters, William. (Tufts University. Tisch Library., 2018)
Presented at Rutgers University in April of 2017, this presentation discusses new data in agricultural research.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy